2019
DOI: 10.1126/sciadv.aav9075
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of biomimetic collagen-ligand interaction to intrafibrillar mineralization

Abstract: Contemporary models of intrafibrillar mineralization mechanisms are established using collagen fibrils as templates without considering the contribution from collagen-bound apatite nucleation inhibitors. However, collagen matrices destined for mineralization in vertebrates contain bound matrix proteins for intrafibrillar mineralization. Negatively charged, high–molecular weight polycarboxylic acid is cross-linked to reconstituted collagen to create a model for examining the contribution of collagen-ligand inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 40 publications
0
47
0
Order By: Relevance
“…Moreover, each group seems to have developed its own mineralization protocol, making it difficult to reproduce experimental results and hampering comparison of results between different papers. Compare, for example, the experiments of Qi et al [107] and Song et al [108] (Table 2). Both use 450 kDa pAA, at a concentration of 50 µg mL −1 in solution, but whereas Qi et al observed intrafibrillar mineralization, Song et al only observed the formation of prenucleation clusters.…”
Section: Conclusion and Perspectivementioning
confidence: 90%
See 1 more Smart Citation
“…Moreover, each group seems to have developed its own mineralization protocol, making it difficult to reproduce experimental results and hampering comparison of results between different papers. Compare, for example, the experiments of Qi et al [107] and Song et al [108] (Table 2). Both use 450 kDa pAA, at a concentration of 50 µg mL −1 in solution, but whereas Qi et al observed intrafibrillar mineralization, Song et al only observed the formation of prenucleation clusters.…”
Section: Conclusion and Perspectivementioning
confidence: 90%
“…When the polymer was in solution, only prenucleation clusters were observed, while crosslinking this high-molecular weight pAA to collagen leads to intrafibrillar mineralization. [108] Crosslinking a low-molecular weight (2 kDa) pAA to collagen leads to full inhibition of HAp mineralization.…”
Section: Intrafibrillar Mineralization Of Collagen With Hydroxyapatitmentioning
confidence: 99%
“…In other studies, the 1082 cm −1 band was assigned to the mutual stretching vibration of the C-O bonds in the carbohydrate as well as to the symmetric PO 2 stretching vibration in the phosphorylated proteins (for a review, see [ 46 ]). The presence of phosphates was also attributed to the bands at 1200–965 cm −1 [ 9 ], 1022 cm −1 [ 47 ], 1020 cm −1 and 960 cm −1 [ 48 ] and also at 500–600 cm −1 [ 9 , 23 , 48 ], while the bands at 872 cm −1 , 873 cm −1 and 1413 cm −1 were assigned to carbonates [ 47 , 48 ]. Similarly, in KBr-FTIR spectra of a human cortical bone, the bands at 1032, 603 and 563 cm −1 were assigned to phosphates, while the band at 872 cm −1 was assigned to carbonates [ 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…It can be attributed to the fact that our mineralization process lasted for a relatively short period, i.e., only 48 h. Even in collagen gels where the mineralization in SBF was enhanced by citric acid, the phosphates started to be detectable after only 3 days of mineralization and were clearly apparent after 7 days, and the carbonates were detectable after only 7 days [ 47 ]. A clear time-dependent mineralization of collagen was also shown by dynamic attenuated total reflection (ATR)–FTIR spectroscopy in collagen sponges subjected for 7 days to an intensive biomimetic intrafibrillar mineralization using a negatively charged polyelectrolyte [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…These cationic polymers are unlikely to bind to the positive net charge of collagen fibrils through electrostatic attraction and facilitate the infiltration of amorphous precursors. A recent work conducted by Song et al [ 71 ] indicated that the zeta potential of collagen bound with high-molecular weight PAA (450 kDa) was –17.17 ± 1.98 eV, while that of CaP precursors was –0.88 ± 0.07 eV. Apparently, attachment of these two negatively charged species cannot be simply explained by electrostatic attractions according to the basis of Coulombic interpretations.…”
Section: Intrafibrillar Mineralization Mechanismsmentioning
confidence: 98%